THE FUNCTION OF SATIRE IN 18TH-CENTURY BRITISH LITERATURE (Modern education and development, 2025)
This article analyzes the role and functions of satire in 18th-century British literature. Through the genre of satire, the article examines social-political criticism, moral values, and the exposure of societal flaws. Using the works of writers such as Jonathan Swift, Alexander Pope, and Samuel Johnson as examples, the power and significance of satire are revealed.